THE INFLUENCE OF MOTIVATION ON ACADEMIC PERFORMANCE OF MUSLIM YOUTH IN ISLAMIC UNIVERSITIES - Rizki Amaliyah; Chairunnisa; Wahyu Agung Hidayatullah; Nurrina Zulfa; Aria Mahardika; Nadia Safana; Anita; Rendi Praja Pratama; Reira Izzatunisa; Cindy Destika; Hanna Wirena Putri; Revalina Stevy (Journal of Islamic Psychology and Behavioral Sciences, 2023)
This study aims to determine the relationship between motivation and academic performance of Muslim youth at Islamic universities. Respondents involved in this study were 104 respondents. The respondents involved in this study were 104 respondents who were randomly selected using data collection techniques used were questionnaires using scales as data collection tools, namely using motivation and academic performance scales. By using correlational quantitative research methods. The results of this study indicate that motivation affects the academic performance of Muslim youth. Because motivation is an encouragement, meaning that where behavior can influence a person's efforts so that his heart acts for him to do something so that there are results. Motivation is very important because it can support a person's behavior so that he wants to work hard, so that he can produce the best.